Utilising a high pressure, cross flow, stainless steel fintube heat exchanger for direct steam generation from recovered waste heat - Wipplinger, Karl Paul Martin (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng) -- Stellenbosch University, 2004.